Unraveling taxonomy of Fissidens sylvaticus and its varieties from India - Jandial, Manchi; Shukla, Darshan; Singh, Sushil Kumar (Phytotaxa, 2025)
The taxonomic status of Fissidens sylvaticus and its varieties known from India are reinvestigated. F. sylvaticus var. teraicola is proposed as a new synonym of F. crispulus var. crispulus. F. sylvaticus var. calcuttense and F. sylvaticus var. auriculatus are proposed to be new synonyms of F. curvato-involutus. A newly described taxon, F. crispulus var. nelliampathiae is also synonymized with F. crispulus var. robinsonii. The diagnostic features of F. taxifolius, F. crispulus and F. curvato-involutus from India have been given along with supportive line-drawing illustrations and photographic plates.